Empowering economic independence: POKDAKAN modernization and market integration in Tanjung Rhu Village, Pekanbaru City - Ulfia Hasanah; Evi Deliana; Indra Lesmana; Selly Prima Desweni; Samariadi Samariadi; Afriani Nazara; Annisa Dwi Chandra; Dara Aiko Damantha; Dwi Liana Rahmayuni; Ika Sulistya Ningrum; M Prima; Prasiswi Ningsih; R Sadiah Maharani; Vito Oktariandi MK; Yulisa Rika Sari (Universitas Muhammadiyah Magelang, 2024)
The